Emotions' influence on customers' e-banking satisfaction evaluation in e-service failure and e-service recovery circumstances. Issue 1 (2022) - Nyagadza, Brighton; Mazuruse, Gideon; Muposhi, Asphat; Chuchu, Tinashe; Makoni, Tendai; Kusotera, Brain
Abstract: Purpose: The growth in electronic banking platforms resulted in the unintended effect of minimising the customer-service provider physical interactions that were instrumental in managing negative emotions emanating from service failure. This study investigates the influence of emotions related to e -service failure and e -service recovery strategies on customer satisfaction. Design/methodology/approach: Cross sectional data was collected from 433 e -banking customers using a structured, respondent administered questionnaire. Respondents were randomly intercepted as they moved out of personal service platforms of four selected banks. Hypotheses were tested using structural equation modelling. Findings: Emotions were found to have a direct positive influence on customers' e -banking satisfaction evaluation during e -service failure and e -service recovery. Research limitations/implications: Research was conducted in Marondera, an agro-based emerging town geographically located in Mashonaland East province of Zimbabwe. The generalisation of the study findings in Zimbabwe may be enhanced by extending the study to other cities. Practical implications: During the formulation of e -service marketing strategies, bank managers are encouraged to consider the influence of emotions on customers' e -banking satisfaction in order to enhance the effectiveness of e -service recovery initiatives. Originality/value: The findings of this study contribute to efforts towards effective management of emotions related to e-service failure and evaluation of e-service recovery strategies, a study area which remains under researched in Zimbabwe's banking sector.